Online Consultations Between General Practitioners and Psychiatrists in the Netherlands: A Qualitative Study - Bock, Nynke W.; Wouters, Hans; Lammers, Anne J.; Blanker, Marco H. (Frontiers in Psychiatry, 2021)
Objective. To examine the nature and scope of questions about psychiatric patient cases submitted by general practitioners (GPs) to an established online consultation platform and to determine if they could have been answered by consulting existing clinical guidelines. Methods. All anonymized psychiatric cases submitted by GPs to the online electronic Prisma platform between September 2018 and November 2019 were examined in a mixed-methods study. Descriptive statistics and qualitative thematic analysis were used, followed by axial coding to arrive at overarching themes to characterize cases. Results. Of the 136 included cases, 44.1% concerned female patients and about half concerned patients aged 31–60 years. Common psychiatric disorders were depression, attention deficit hyperactivity disorder, sleeping problems, sexual disorders, and eating disorders. The first response was usually given within 2 hours (interquartile range, 0–14.3 hours), with 86% answered within 24 hours and 95% within 48 hours. Qualitative analysis revealed four themes, namely “type of question,” “cases in relation to current clinical guidelines,” “case complexity” and “the doctor being pressured.” Type of question comprised diagnostic, therapeutic, and referral questions. Notably, for 44.1% of questions no current clinical guidelines was present and 46.3% of cases were deemed complex in nature. GPs were willing to share their experiences of coping with being pressured by patients. Conclusion. The findings of this study support the potential for an online electronic consultation platform to facilitate feasible and useful interprofessional consultation between GPs and psychiatrists for a broad range mental illnesses and questions of varying complexity.